Perspective taking in language: When bodily involvement impacts motion events’ descriptions (Signifiances (Signifying), 2017)
Speakers’ linguistic apprehension of the world tends to be circumscribed by the language they use, a language that mirrors speech habits, structured by lexical and morphosyntactic patterns. To this respect, when structuring the domain of space through language, English verbs and satellites foreground the action and background the purpose (swim across a river), whereas French linguistic features foreground the aim and background the act (traverser la rivière à la nage); both linguistic patterns giving hence precisions on the relationship held between the speaker and his body according to what is preferentially highlighted in the language used. These linguistic patterns illustrate the Talmian typology which opposes satellite-framed languages like English, to verb-framed languages like French. To further investigate this typology, distinguishing phrases structured differently to refer to motion events (Talmy, 2000) according to the type of language used, an experiment soliciting English and French spoken corpora aims at demonstrating whether the affiliation of a language to a specific language type (e.g. English as a satellite-framed language) determines or not the embedding of the language examined to this specific affiliation, once the speech is actually implemented in discursive contexts.